Tourism revenues and economic growth: a panel data analysis of Mediterranean coastal countries - TANKUŞ, Emre; ÖZTÜRK, İlker; ALTUNÖZ, Utku; KOÇ, Selahattin; SÖKMEN, Alptekin (University of Rijeka, Faculty of Tourism and Hospitality Management, 2025)
Purpose – This study examines the impact of tourism revenues on economic growth in Mediterranean coastal countries from 2000 to 2022 using panel data methodology. By encompassing various economic cycles and significant global events, this research provides a comprehensive analysis of both short-term and long-term effects of tourism receipts on GDP. Methodology – In the study, 10 countries in the Mediterranean (France, Italy, Spain, Türkiye, Greece, Tunisia, Egypt, Morocco, Malta and Algeria) were selected by simple random sampling method. Annual data covering the period 2000-2022 were used in the analyses and the panel ARDL method was used to reveal the purpose of the study. Findings – The panel ARDL method reveals that tourism revenues significantly boost economic growth, emphasizing the tourism sector's critical role in fostering development. These findings offer crucial insights for policymakers, stakeholders, and investors in the Mediterranean region's economic dynamics. Originality – The study contributes to the literature by utilizing recent data and multiple variables to capture the nuanced relationship between tourism and growth.
Keywords: Tourism, Economic Growth, Panel Data Analysis, Mediterranean, ARDL; tourism; mediterranean; panel data analysis; economic growth; ardl; Hospitality industry. Hotels, clubs, restaurants, etc. Food service; TX901-946.5